Cancer of the tongue and floor of the mouth: Current aspects of diagnosis - A. L. Yudin; R. A. Shсhetinin; N. I. Afanas'eva (Вестник рентгенологии и радиологии, 2016)
The diagnosis and treatment of cancer of the tongue and floor of the mouth is a relevant problem, for 60–80% of patients first seek medical treatment only when they have late stages of the disease. The review analyzes the data available in the Russian and foreignliterature on mainstay techniques for radiodiagnosing cancer of the mouth and floor of the mouth. It highlights the capabilities of computed tomography in diagnosing this pathology, in assessing deepseated anatomic structures of the mouth and floor of the mouth, and in detecting metastatic neck lymph nodes.